Research progress of health education of integrated traditional Chinese and Western medicine for patients with chronic obstructive pulmonary disease at stable stage (中西医结合健康教育在慢性阻塞性肺疾病稳定期患者中应用的研究进展) - ZHU Suran (朱素然) (Association of Integrative Nursing, 2024)
Chronic obstructive pulmonary disease (COPD) is a common lung disease causing restricted airflow and breathing problems. COPD treatment focuses on minimizing further lung damage, controlling symptoms and preventing complications. Health education is an important component of pulmonary rehabilitation for COPD patients at stable stage. This paper reviewed domestic and foreign studies on health education for COPD patients, analyzed the role of constitution and Traditional Chinese Medicine syndrome differentiation in individualized health education, and provided reference for establishment of health education of integrated traditional Chinese and Western medicine for phlegm-dampness syndrome patients with COPD at stable stage. (慢性阻塞性肺疾病是临床常见呼吸系统疾病, 积极预防以及延缓病情发展是防治关键。健康教育在慢性阻塞性肺疾病稳定期患者的康复管理中有着重要作用。本研究就慢性阻塞性肺疾病稳定期的健康教育现状进行总结, 分析体质辨识在个体化健康教育中的作用, 以期为制定痰湿体质慢阻肺稳定期患者的中西医结合健康教育方案提供参考。)